Novel Multidisciplinary Salivary Gland Society (MSGS) Questionnaire: An International Consensus. Issue 2 (8th July 2021) - Buchholzer, Samanta; Faure, Frédéric; Tcheremissinoff, Livia; Herrmann, François R.; Lombardi, Tommaso; Ng, Siu‐Kwan; Lopez, Jean‐Michel; Borner, Urs; Witt, Robert L.; Irvine, Robert; Abboud, Olivier; Cernea, Claudio R.; et al.
Abstract : Objectives: First, establishment and validation of a novel questionnaire documenting the burden of xerostomia and sialadenitis symptoms, including quality of life. Second, to compare two versions regarding the answering scale (proposed developed answers Q3 vs. 0–10 visual analogue scale Q10) of our newly developed questionnaire, in order to evaluate their comprehension by patients and their reproducibility in time. Study Design: The study is a systematic review regarding the evaluation of the existing questionnaire and a cohort study regarding the validation of our new MSGS questionnaire. Materials and Methods: A Multidisciplinary Salivary Gland Society (MSGS) questionnaire consisting of 20 questions and two scoring systems was developed to quantify symptoms of dry mouth and sialadenitis. Validation of the questionnaire was carried out on 199 patients with salivary pathologies (digestive, nasal, or age‐related xerostomia, post radiation therapy, post radioiodine therapy, Sjögren's syndrome, IgG4 disease, recurrent juvenile parotitis, stones, and strictures) and a control group of 66 healthy volunteers. The coherence of the questionnaire's items, its reliability to distinguish patients from healthy volunteers, its comparison with unstimulated sialometry, and the time to fill both versions were assessed. Results: The novel MSGS questionnaire showed good internal coherence of the items, indicating its pertinence: the scale reliability coefficients amounted to a Cronbach's alpha of 0.92 for Q10 and 0.90 for Q3. The time to complete Q3 and Q10 amounted, respectively, to 5.23 min (±2.3 min) and 5.65 min (±2.64 min) for patients and to 3.94 min (±3.94 min) and 3.75 min (±2.11 min) for healthy volunteers. The difference between Q3 and Q10 was not significant. Conclusion: We present a novel self‐administered questionnaire quantifying xerostomia and non‐tumoral salivary gland pathologies. We recommend the use of the Q10 version, as its scale type is well known in the literature and it translation for international use will be more accurate. Laryngoscope, 132:322–331, 2022